The IPO Market in India: Perspective, Prospects, and Growth Strategies - Gupta, Ambrish (Indian Journal of Finance, 2013)
The paper has assessed the present state of the primary capital market in India, main reasons responsible for the continuing gloom, and its likely future outlook. Some suggestions have been made for its long-term growth and development, which revolve around policies of the Securities and Exchange Board of India relating to free pricing (resulting in greedy overpricing of equity issuances), incomprehensive grading of initial public offerings, institutional placement programme, offer for sale (stock exchange auction system), and malpractices of the government. What emerges clearly is the need on the part of Securities and Exchange Board of India (SEBI) to introspect and carry out with determination an unbiased review of its primary capital market policies and suitably reform them to promote the market and also to ensure the sustained interest, faith, and confidence of the investors. The government also needs to exercise self-control on its unfair trade practices in the primary capital market and keep the public interest as supreme.